Fa'ālῑyat istikhdām 'ard al-suwar fῑ tadrῑs al-mufradāt ladā tullāb qism al i'dād al-lughawῑ bῑ jāmi’ati al- rāyah - Muhammad Khanif; Muhammad Farhan Bahrun; Mukhlishoh (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
this study aims to assess the effectiveness of one visual teaching method, namely the use of picture presentation, among students in the Language Preparation Department at Al-Raya University. This research adopts a field study approach, utilizing a quantitative method with an experimental design involving a single group, including pretest and posttest evaluations. The study's findings indicate that the statistical results of the Wilcoxon test reveal an Asymp.Sig (2-tailed) value of 0.001, which is smaller than <0.05. Consequently, it can be concluded that the hypothesis is accepted, suggesting a difference between the results of vocabulary learning in the pretest and posttest. Additionally, the study reveals that the average standardized progress score is 0.75, implying a high level of standardized progress for the proposed hypothesis. Therefore, it can be inferred that the use of picture presentation as a teaching method has an impact on the results of vocabulary learning among students in the Language Preparation Department at Stiba Al-Râyah, indicating the effectiveness of teaching vocabulary through picture presentation.